SIMBOL AGAMA DALAM FILM PK PERSPEKTIF MEANING DAN MEDIA - Iwan Setiawan (JURNAL AT-TURAS, 2014)
In film PK found, first symbol of religion that be in earth so many and confuse. The second, in structuralist, every religion have rule culture that not the same and potentially give rise to conflict. In this film pictured taht this religious leader that connect between believer with his Lord. The third, in connotative the film PK want criticize reality of religion that confound and better believe in God without that Religious ties. The Film PK constitute reflection and sharp criticism to religion in the earth. The religion become road that confuse towards the God, becouse many differences. Even, the religion through His religion leaders apply road that difficult even no provide solutions for the life. Should, the religion no become source conflict and source income for religious leader. Should, the religion truly become solutions and easy street and straight towards the God.